Properties of particle and strand board from hevea brasiliensis and leucaena leucocephala / Muhammad Rahman Mohd Tahir - Mohd Tahir, Muhammad Rahman (2012)
This study used Rubberwood and Leucaena spp wood as a raw material in the manufacture of particle, hybrid (particle + strand) and strand board (OSB). Currently rubberwood supply is getting depliting and limited in resources. Thus, Leucaena spp was mix with rubberwood in order to counter depliting supply of rubberwood as a alternative spp to produce a boards. The objectives of this study are to determine the properties and evaluate the potential of this boards. Target board density was 700 kg/m3 with applied 10% of Urea Formaldehyde as a binder. The quality of the boards were evaluated by determine of bending properties including modulus of elasticity (MOE), modulus of rupture (MOR), internal bond (IB) strength, thickness swelling (TS) and screw withdrawal (SW) based on BS EN standard. All of the results testing was achieved the standard requirement except for thickness swelling (TS).